Biodegradation of three different collagen membranes: A histological study - A. Olaechea; G. Mendoza-Azpur; E. Valdivia; G. Rasperini (Ariesdue, 2016)
Aim The aim of this study was to evaluate in vivo the absorption rate of three membranes: bovine collagen (GenDerm, Baumer, Brazil), collagen (Genoss, Dentium, Korea) and porcine dermis membrane (Kytinon M.O.R., Asmopul, Argentina). The additional aims were to evaluate blood vessel penetration and fiber collagen penetration in the early wound healing process. Materials and Methods Four dogs were used for the study and the membranes were applied by subperiosteal placement and analyzed after 15, 30, 60 and 90 days. Results The absorption rate of <35% at 15 days was similar for all the membranes. At 30 days, rates between 35% and 65% were observed. After 60 days, only the bovine collagen membrane (GenDerm, Baumer SA, Brazil) was found to have achieved >65% absorption. This bovine collagen membrane was completely absorbed after 90 days. At this time point absorption of the bovine collagen (Collagen®, Dentium, Korea) was >65%, while absorption of the porcine dermis (Kytinon®, Asmopul, Argentina) was found to be between just 35% and 65%. Conclusion Blood vessel penetration and fiber collagen penetration in the three membranes showed significant differences, with faster vascularization and collagen penetration in the more rapidly absorbed membranes.